Classifying colonial populations in Asia. The censuses of the Portuguese State of India in the early 18th century - Matos, P. T. de (The 3rd European Society of Historical Demography Conference, 2019)
- A census for the Portuguese State of Índia (Estado Português da Índia) in 1720? - Who instructs the census and who carries it out? - Data quality and structure: territorial, social and religious coverage, permanent population and “fluctuating populations”. - Categorizing the Portuguese ‘Asian’ Populations (Estado Português da Índia) - Preliminary conclusions